2002
DOI: 10.1002/pon.562
|View full text |Cite
|
Sign up to set email alerts
|

Predicting major depression in brain tumor patients

Abstract: Very few studies have been performed utilizing DSM criteria to diagnose major depressive disorder (MDD) in adult brain tumor patients. This study aimed to diagnose MDD in this population using DSM-IV criteria.Eighty-nine adult brain tumor patients were examined in an ambulatory neuro-oncology clinic setting using a structured psychiatric interview which followed current DSM-IV diagnostic criteria for MDD. This sample was interviewed and evaluated on a one-time basis. The patients were referred for evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
2
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 21 publications
2
68
2
9
Order By: Relevance
“…For our non-frontal patients the mean score on the HADS depression subscale was lower than all but one of the studies reported by Rooney et al [20]. Although there is currently no consistent evidence that tumour location and depression are associated, the study by Wellisch et al [28] reported that frontal lobe tumour location was independently associated with major depressive disorder using DSM-IV criteria. The neurobehavioural changes following brain tumour reported by a substantial percentage of both relatives of and patients with brain tumours in our study highlight the need for support and management for relatives as much as patients.…”
Section: Discussioncontrasting
confidence: 61%
“…For our non-frontal patients the mean score on the HADS depression subscale was lower than all but one of the studies reported by Rooney et al [20]. Although there is currently no consistent evidence that tumour location and depression are associated, the study by Wellisch et al [28] reported that frontal lobe tumour location was independently associated with major depressive disorder using DSM-IV criteria. The neurobehavioural changes following brain tumour reported by a substantial percentage of both relatives of and patients with brain tumours in our study highlight the need for support and management for relatives as much as patients.…”
Section: Discussioncontrasting
confidence: 61%
“…The reported prevalence of clinically significant depressive symptoms in patients with brain tumors varies from 15 to 44% (1,18,24,33). Symptoms of anxiety are even more common, affecting up to 62% of patients with primary brain tumor before surgery (7,20,26).…”
Section: Introductionmentioning
confidence: 97%
“…Pourtant, les liens entre dépression et plus généralement troubles de l'humeur et atteinte tumorale céré-brale sont connus bien que le plus souvent rapportés sous forme de cas cliniques (case report) [65,126]. Les troubles dépressifs sont soit le fait de la localisation tumorale au niveau du lobe temporal et de l'hémisphère droit [120], du lobe pariétal [64] ou frontal [126] soit du fait des antiépilep-tiques associés et reconnus comme étant dépressogènes [70,119].…”
Section: Cas Particulier : Antidépresseurs Et Tumeurs Cérébralesunclassified